PERSEPSI ANAK ASUH TERHADAP POLA ASUH PEMBINA PANTI ASUHAN AS-SHOHWAH DI KELURAHAN SIMPANG BARU KECAMATAN TAMPAN KOTA PEKANBARU - Arie Susanti; Desti Irja; Titi Maemunaty (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Research it is based on the state of perception foster care to foster pattern trustees orphanage seen from the types pattern foster. Because of the foster pattern is characteristic the base that must be is used to development perception foster care to foster pattern trustees orphanage As-Shohwah in Kelurahan Simpang Baru Kecamatan Tampan the city of Pekanbaru. Formulation of the problem of this study is whether the perception foster care to foster pattern coaching an orphanage As-Shohwah in Kelurahan Simpang Baru Kecamatan Tampan the city of Pekanbaru have good discipline?. The purpose of this research is to know the perception foster care to foster pattern coaching an orphanage As-Shohwah in Kelurahan Simpang Baru Kecamatan Tampan the city of Pekanbaru have good discipline.Population in this study as many as 37 people foster care. Then the researcher determine samples from 37 people for research and 20 people to the tests of somewhere else, with uses the technique of sampling saturated. An instrument data collection namely poll with 60 a statement and if the trial live 53 a statement that valid to make instrument in research. Through data analysis of the quantitative descriptive analysis. The outcome of research on three indicators a conclusion can be drawn that the perception foster care to foster pattern coaching an orphanage As-Shohwah in Kelurahan Simpang Baru Kecamatan Tampan the city of Pekanbaru have good discipline, with the highest indicators first foster pattern democratic look at of keeping kerhamonisan obtained value a percentage (the ss + s) 98 %. It means children assume keep harmony is very important.Key words: Perception , perception foster care to foster pattern trustees orphanage